Multiple perspective co-citation analysis on the Big Data analytics theme - Vaz, Arthur Moura; Bachega, Stella Jacyszyn; Tavares, Dalton Matsuo (Brazilian Journal of Production Engineering, 2023)
One of the technologies of industry 4.0 is Big Data Analytics, which allows transforming a large number of different types of data into valuable information with potential for decision-making, innovation, among others. In this context, the objective of the article is to present an analysis of co-citations in multiple perspectives on the theme Big Data Analytics. For that, we used the hypothetical-deductive scientific explanation, a mixed qualitative and quantitative research approach and the method of analysis of co-citations in multiple perspectives, using the CiteSpace® software. We considered 11 full years of publications, and the ones already available in the current year of the Web of Science (WoS) search. We verified the main lines of research on the subject, the main authors, the prominent keywords, the timeline of studies in the main areas of research and the leading countries in publications. The study showed the existence of a strong relationship between Big Data Analytics and Supply Chain Management, being a great indication of the influence of this technology in the productive sector. Among the contributions, this research points out possibilities and advantages of applying large data analysis and its challenges.
Keywords: Big Data Analytics; CiteSpace; Multiple Perspective Co-Citation Analysis; Industry 4.0